Inference Algorithms for Similarity Networks - Geiger, Dan; Heckerman, David (Morgan Kaufmann Publishers, 1993)
We examine two types of similarity networks each based on a distinct notion of relevance. For both types of similarity networks we present an efficient inference algorithm that works under the assumption that every event has a nonzero probability of occurrence. Another inference algorithm is developed for type 1 similarity networks that works under no restriction, albeit less efficiently.
Proceedings of the IEEE International Conference on Data Mining (ICDM)